The Influence of Indian Ocean Dipole on Surface Wind Speed Variation in Coastal South China - Yan Shengjiang; Xie Yu; Zhou Houyun (Redai dili, 2024)
Wind speed is an important parameter reflecting the climate and environmental conditions on the Earth's surface. It is also a pivotal factor influencing wind energy, a renewable and clean energy source. The mechanisms exerting influence on the surface wind speed over China, which have been mentioned in previous studies, include the temperature difference between the high and low latitudes of China, surface drag force, and climatic factors such as the Arctic Oscillation (AO), Pacific Decadal Oscillation (PDO), and El Niño-Southern Oscillation (ENSO). The Indian Ocean Dipole (IOD), which has attracted increasing attention during the past two decades, is an important climatic factor that exerts a significant influence on the climate and environment in the areas surrounding the Indian Ocean and globally. However, to date, it has not been reported whether the IOD is a climatic factor that significantly affects surface wind speed in China. Coastal South China is one of the most economically developed areas in China, and wind energy is becoming an important energy source in this area. An investigation of the relationship between the IOD and wind speed variations in coastal South China and their connecting mechanisms would contribute substantially to the understanding of the controlling mechanisms of climatic and environmental variations in coastal South China as well as to the planning of sustainable development in this area. Based on observations of surface wind speed in coastal South China, reanalysis data from the National Center of Environment Prediction (NCEP) and the National Center of Atmospheric Research (NCAR), research on the IOD over the last two decades, the effects of IOD activities on surface wind speed in coastal South China, and the controlling mechanisms were investigated using statistical analyses and atmospheric circulation variations. The results indicate that, regardless of the temporal or spatial scale, variations in the surface wind speed in coastal South China show significant positive correlations with the dipole mode index (DMI), which is a proxy for IOD activity. An increase in the DMI index (indicating a strengthening of IOD activity) corresponds to a decrease in the surface wind speed in coastal South China, and vice versa. This suggests that, in addition to the factors suggested in previous studies, which include the temperature difference between high and low latitudes, AO, PDO, and ENSO, IOD activity is also one of the most important factors affecting surface wind speed variation in coastal South China. The influence of IOD activity was weaker than that of the temperature difference between high and low latitudes. However, it played a more important role in the surface wind speed variation in this region than the AO, PDO, and ENSO. Strengthening of the IOD activity would enhance two anti-cyclones in the northwest Pacific and Bengal Bay, east of the Indian subcontinent, and, in turn, contribute to the reduction of surface wind speed variation in coastal South China. More serious global warming and increasing greenhouse gas emissions will further strengthen IOD activity in the future. Consequently, a greater decline in surface wind speed is expected in coastal South China, necessitating attention to sustainable wind energy use in this region.